The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s10686-015-9442-5
|View full text |Cite
|
Sign up to set email alerts
|

Hard X-ray polarimetry with Caliste, a high performance CdTe based imaging spectrometer

Abstract: Since the initial exploration of the X-and soft γ-ray sky in the 60's, high-energy celestial sources have been mainly characterized through imaging, spectroscopy and timing analysis. Despite tremendous progress in the field, the radiation mechanisms at work in sources such as neutrons stars, black holes, and Active Galactic Nuclei are still unclear. The polarization state of the radiation is an observational parameter which brings key additional information about the physical processes in these high energy sou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The Q factor obtained is found to be 0. [11]. When compared with other CdTe-based planar polarimeters, we obtain a better polarization Q factor (Curado da Silva et al 2008) [12].…”
Section: Caliste Polarization Performance In 200-300 Kev Energy Rangementioning
confidence: 63%
“…The Q factor obtained is found to be 0. [11]. When compared with other CdTe-based planar polarimeters, we obtain a better polarization Q factor (Curado da Silva et al 2008) [12].…”
Section: Caliste Polarization Performance In 200-300 Kev Energy Rangementioning
confidence: 63%
“…15, in the energy band between 80 keV and 600 keV, and setting Q 100 = 0.6. The latter is a realistic value for the NFT required focal plane, as can be inferred from different experiments performed using CdTe spectro-imagers operated as scattering polarimeters [4,24]. Figure 16 shows this estimate as a function of both the observing time for a 10 mCrab source, and the source intensity integrated over 10 5 s. A Crab-like spectrum is assumed, with a background level given by [26] and later confirmed with the INTEGRAL SPI instrument, scaled to a low-Earth orbit.…”
Section: Expected Nft Performance -Sensitivity To Continuum Emissionmentioning
confidence: 91%
“…The quality (modulation factor) of a scattering polarimeter is strictly dependent on his spatial resolution and spectroscopic performance. Several experimental measurements [16,17,18] and simulation model have demonstrated that a detector allowing a good selection of events using both the spectroscopic and position information of each hits can achieve very high modulation factor. In particular the possibility to select events within thin layer of the sensitive volume, thanks to the intrinsic 3D segmentation of the detector (i.e.…”
Section: Considerations On 3d Czt Spectrometers Applicationsmentioning
confidence: 99%